(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
This study aimed to test the impact of strategic agility on the competitive advantage in the commercial banks operating in the southern region. The study used the descriptive analytical approach, by conducting a comprehensive survey of the study population of 166 respondents. The number of questionnaires suitable for analysis reached (126) respondents. The Statistical Package for Social Sciences was used to find the values ​​of arithmetic means, standard deviations, and multiple regression analysis. The study reached results, the most important of which were that managers’ perceptions of strategic agility and competitive advantage were high, and that there was an impact of strategic agility in its dimensions (strategic sensitivity, organizational capabilities, and strategic responsiveness) on competitive advantage in its dimensions (cost leadership, excellence, focus, and creativity), which accounts for 69.7% of the change in competitive advantage. The study recommends the necessity of adopting the concept of strategic agility, working to invest in it, and adopting policies and procedures that will achieve the competitive advantage.